The The Effect Of Work Discipline, Work Environment, And Work Motivation On Employee Performance At Bintang Mulia Hotel Bagan Batu - Dani Sucipto; Yuniman Zebua (International Journal of Business and Quality Research, 2026)
This study aims to analyze the effect of work discipline, work environment, and work motivation on employee performance at Bintang Mulia Hotel Bagan Batu, both partially and simultaneously. The method used is descriptive quantitative with total sampling of 60 respondents, data collection through a Likert scale questionnaire, and analysis using multiple linear regression with SPSS version 26. The results show that work discipline has a positive and significant effect on employee performance (t=12.312; sig=0.000), work environment has a positive and significant effect on employee performance (t=2.888; sig=0.006), work motivation has a positive and significant effect on employee performance (t=4.167; sig=0.000), and simultaneously all three variables have a positive and significant effect on employee performance (F=541.795; sig=0.000) with an R² value of 0.967, meaning 96.7% of the variation in employee performance is explained by these three variables. The findings of this study reveal that work discipline is the most dominant factor influencing employee performance, thus consistent application of work discipline, a conducive work environment, and strong work motivation are the main keys to improving employee performance in the hospitality industry.